New Records of Epiphytic Lichens from Three Districts of Assam, India - Daimari, Rebecca; Hazarika, Natasha; Hoque, Raza R.; Nayaka, Sanjeeva; Upreti, Dalip K. (Indian Forester, 2014)
Distribution of epiphytic lichens from three districts of Assam viz. Baksa, Kamrup and Sonitpur have been enumerated for the first time from eleven locations. A total of 67 species belonging to 12 families and 24 genera have been recorded. Of the total species, crustose, foliose and leprose lichens represented 60%, 39% and 1% respectively. The family Physciaceae emerged to be the most dominant, with a total of 20 species followed by Graphidaceae with 16 species. Patkijuli location revealed to have the highest lichen diversity followed by Nameri National Park. A total of 41 lichen taxa are new records for Assam.